PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN: THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, COMPANY SIZE, AND SALES GROWTH ON COMPANY VALUE - Awaludin, Dipateruna Teruna; Hasanudin, Hasanudin; Ramli, M; Wulandari, Rizma (JURNAL REKAYASA INFORMASI, 2025)
ABSTRACT This research aims to analyze whether there is an influence of corporate social responsibility, company size, and sales growth on the value of the company. The population in this study is a manufacturing company in the consumer goods industry sector listed on the Indonesia Stock Exchange. The sampling technique in this study uses purposive sampling and the sample used consists of 155 companies observation period conducted 2016-2020. The type of data in this study is secondary data that uses data from financial statements. The technical data analysis used in this study is multiple linear regression analysis and the data is processed using the SPSS program version 23.0. The results of this study showed that corporate social responsibility had no effect on the value of the company, and sales growth had no effect on the value of the company. While the size of the company positively affects the value of the company.. Keywords : Corporate Social Responsibility, Company Size, Sales Growth.